Thomas Luckmanns Auffassung bezüglich des Verhältnisses von Phänomenologie und Soziologie: Eine kritische Betrachtung ihrer Stärken und Schwächen - Gros, Alexis Emanuel (2020)
In the present paper, I intend to systematically revisit Thomas Luckmann’s account of the relation between phenomenology and sociology, and to assess its strengths and weaknesses in terms of a constructive criticism. In order to achieve this aim, I will proceed in three steps. First (1), I will reconstruct his position by means of an exhaustive analysis of his programmatic texts. Second (2), I will identify its strengths and merits. And finally (3), I will expound its shortcomings and try to correct them by bringing Luckmann into dialogue with other sociological-theoretical and phenomenological accounts.